Radar automatic target recognition (ATR) and non-cooperative target recognition (NCTR) - Blacknell, David; Griffiths, H. (Hugh), 1956- (IET radar, sonar, navigation and avionics series ;, 2013)
The ability to detect and locate targets by day or night, over wide areas, regardless of weather conditions has long made radar a key sensor in many military and civil applications. However, the ability to automatically and reliably distinguish different targets represents a difficult challenge. This book presents an overview of the state-of-the-art and continuing challenges of radar target recognition.